1978
DOI: 10.1128/aac.14.3.420
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial Activities of Various 4-Pyridinemethanols with Special Attention to WR-172,435 and WR-180,409

Abstract: Pilot appraisals of the activities of 10 specially selected 2,6-substituted-4-pyridinemethanols against acute Plasmodium falciparum infections in owl monkeys identified three derivatives that were two to three times as active as chloroquine against infections with a 4-aminoquinoline-susceptible strain and, at the same doses, were equally effective against infections with a strain fully resistant to treatment with maximally tolerated doses of chloroquine, quinine, and pyrimethamine. Two of these derivatives, 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…When the tested 4-pyridinemethanols (compounds 4 to 7) were ranked in the order of their activities, a pattern was observed in our study that was similar to that observed in studies carried out in Plasmodium falciparum-infected owl monkeys (28). In more detail, enpiroline was found to be the most active representative followed by compound 5 showing moderate activity and compound 6 showing only minimal activity against P. falciparum.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…When the tested 4-pyridinemethanols (compounds 4 to 7) were ranked in the order of their activities, a pattern was observed in our study that was similar to that observed in studies carried out in Plasmodium falciparum-infected owl monkeys (28). In more detail, enpiroline was found to be the most active representative followed by compound 5 showing moderate activity and compound 6 showing only minimal activity against P. falciparum.…”
Section: Discussionsupporting
confidence: 86%
“…Details on in vitro cytotoxicity assessments performed using two different cell lines are provided in Tables S1 and S2 in the supplemental material. Previous studies have shown that threo enpiroline has acceptable levels of acute and subacute toxicity in mice (28). In addition, the drug was well tolerated in clinical trials using total dosages of 1,500 mg (7).…”
Section: Discussionmentioning
confidence: 88%
“…This subgroup included 22 treated subjects and 3 untreated controls. The remaining 19 monkeys, all previously infected with the Oak Knoll strain of P. falciparum and cured via treatment with a 4-quinolinemethanol or 4-pyridinemethanol (11,13), were used for studies with the Palo Alto strain of P. vivax. Fifteen of the 19 (14 treated and 1 untreated control) were employed in the primary ANTIMICROB.…”
Section: Methodsmentioning
confidence: 99%
“…Second, resistance to floxacrine emerges rapidly, at a rate not less than that of proguanil or pyrimethamine (16,17), compounds that have presented resistance problems in field use. Third, by comparison, floxacrine is a weak competitor of a group of aminoalcohols which have been studied in depth in the same animal models (11)(12)(13)(14). Some have already exhibited promise in limited clinical trials (11,12).…”
mentioning
confidence: 99%
“…Enpiroline has demonstrated significant activity against both the chloroquine-susceptible and the multidrug-resistant forms of P. falciparum. In owl monkeys enpiroline phosphate exhibited a dose which cures 90% of the animals of approximately 30 mg/kg against the multidrugresistant Vietnam Smith strain of P. falciparum when administrated as a single oral dose on 3 consecutive days (17). In human studies enpiroline phosphate was effective against induced multidrug-resistant Vietnam Smith P. falciparum infections (3).…”
mentioning
confidence: 99%